Exploring Natural Plant Products as a Source for Novel Antibiotics - Golakia, Srinidhi Sai (Journal of Research in Science and Engineering, 2026)
This experiment aimed to explore natural alternatives to conventional antibiotics, particularly in addressing the growing issue of bacterial resistance. By testing common natural products for their antimicrobial properties, the study evaluates their potential to serve as effective antibiotics against Bacillus subtilis, Bacillus megaterium, and Escherichia coli. Filter paper discs were infused with garlic, Manuka honey, tea tree oil, clove, and ginger, and placed on bacterial cultures to measure the zones of inhibition. The size of the inhibition zone indicated the efficacy of each natural product in halting bacterial growth. Tea tree oil demonstrated the highest antibacterial activity, producing inhibition zones of 5.23 mm and 10 mm against the tested bacteria. In contrast, Manuka honey and ginger showed no significant inhibitory effects. The findings suggest that certain plant - based products, particularly tea tree oil, can be effective in combating bacterial growth, offering a natural alternative to conventional antibiotics. This approach could contribute to reducing the emergence of antibiotic - resistant superbugs and promote immunity when used consistently.